Liberia : Third Review Under the Extended Credit Facility Arrangement and Request for Waiver of Nonobservance of Performance Criterion and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report, 2014)
This paper focuses on Liberia's Third Review Under the Extended Credit Facility (ECF) Arrangement and Request for Waiver of Nonobservance of Performance Criterion (PC) and Modification of Performance Criteria. Real GDP grew at 8.7 percent in 2013 and is projected to decline to 5.9 percent in 2014 as mining production decelerates. Most end-December 2013 PCs and indicative targets (ITs) were met, except for the PC on government revenue and the IT on external borrowing. Four out of five structural benchmarks were met on time. The IMF staff supports the completion of the third ECF review.